Adsorption of Anionic Surfactants onto Alumina: Characteristics, Mechanisms, and Application for Heavy Metal Removal - Thi Minh Thu Nguyen; Thi Phuong Thao Do; Thi Sim Hoang; Ngoc Viet Nguyen; Huy Dong Pham; Trung Dung Nguyen; Thi Ngoc Mai Pham; Thanh Son Le; Tien Duc Pham (International Journal of Polymer Science)
We investigated adsorption of anionic surfactants, sodium dodecyl sulfate (SDS) and sodium tetradecyl sulfate (STS), onto alumina (Al2O3) with large size in the present study. The effective conditions for SDS and STS adsorption onto Al2O3 were systematically studied. The conditions for SDS and STS adsorption onto γ-Al2O3 were optimized and found to be contact time 180 min, pH 4, and 1 mM NaCl. Adsorption of both SDS and STS onto large Al2O3 beads increased with an increase of ionic strength, demonstrating that the adsorption is controlled by electrostatic attraction between anionic sulfate groups and positively charged Al2O3 surface, as well as hydrophobic interactions between long alkyl chains of surfactant molecules. Nevertheless, the hydrophobic interaction in terms of STS adsorption is much higher than that of SDS adsorption. The obtained SDS and STS adsorption isotherms in different NaCl concentrations onto Al2O3 beads were fitted well by two-step adsorption. Adsorption mechanisms were disused in detail on the basis of adsorption isotherm, the change in surface charge, and the change in functional surface groups by Fourier-transform infrared spectroscopy (FTIR). The application of surfactant adsorption onto Al2O3 to remove cadmium ion (Cd2+) was also studied. The optimum conditions for Cd2+ removal using surfactant-modified alumina (SMA) are pH 6, contact time 120 min, and ionic strength 0.1 mM NaCl. Under optimum conditions, the removal efficiency of Cd2+ using SMA increased significantly. We demonstrate that SMA is a novel adsorbent for removal of Cd2+ from aqueous solution.